Acoustic Characterisation of Individual Targeted Microbubbles with High-Frequency Ultrasound - Sprague, MR; Goertz, D; Cherin, E; Karshafian, R; Foster, F; IEEE (2008)
The acoustic response of individual targeted microbubbles, sized optically, to high-frequency ultrasound was examined to improve nonlinear imaging techniques and aid signal quantification. Single bound phospholipid shell microbubbles (diameters 1.0 to 5.0 mu;m) were insonated with 30 MHz Gaussian-shaped pulses for pressures from 20 kPa to 4 MPa with a fractional-6dB one-way bandwidth of 20%. The scattering cross-section, subharmonic and second harmonic SNR, and microbubble disruption (determined acoustically and verified optically) was measured. The effective scattering cross-section was found to be, on average, 2 times lower than the geometric cross-section; showing size-independent variability. The subharmonic signal increased above the noise floor at 150 kPa, showing a clear peak around 1.5 mu; m; the behaviour at pressures above 400 kPa was more complex. The second harmonic SNR appeared to arise predominately from the presence of nonlinear propagation. The disruption threshold was size-depennt, 400 ± 200 kPa for microbubbles less than 1.5 mu;m in diameter and over 2 MPa for microbubbles larger than 2.5 mu;m. ©2008 IEEE.